Assessing the Distribution and Sustainable Exploitation of Lophius litulon in Marine Areas Off Shandong, China - Zhang, Zhaopeng; Wang, Yuanchao; Liu, Shude; Liang, Cui; Xian, Weiwei (Frontiers in Marine Science, 2022)
In recent years, the proportion and economic value of Lophius litulon (family Lophiidae) in the coastal fishery off Shandong Province, China has increased. In this study, we mapped the distribution of L. litulon abundance [catch per unit effort (CPUE)] and applied a generalized additive model (GAM) to explore the relationship between CPUE and environmental factors. Two data-limited methods (the BSM related to the CMSY method and the AMSY method) were used to evaluate the stock status and relevant fishery reference points of L. litulon. The results showed that the L. litulon stock was concentrated in the central Yellow Sea, at 34.0°–37.0° N and 121.0°–124.0° E, and the highest average CPUE of L. litulon in this area occurred in winter. The three most significant environmental factors affecting species abundance were bottom temperature, bottom salinity, and depth. L. litulon was most abundant when bottom temperature ranged from 5.8 to 10.6°C, depth was > 18 m, and bottom salinity varied from 31.0 to 33.2‰. The BSM and AMSY models indicated that the L. litulon stock was unhealthy and had been overfished in recent years, as its biomass remained below the level that can support maximum sustainable yield. The relative exploitation ratios were also high. These results provide the basic data for improving sustainability of the exploitation of L. litulon in the Yellow and Bohai Seas.